Self Concept Emotional Intelligence and Peer Conformity Among Junior High Students: The Relationship Between Self-Concept and Emotional Intelligence with Peer Conformity Among Students in Junior High School 2 Tanggulangin, Sidoarjo. - Mirza Asyraqi Rahman; Widyastuti (Academia Open, 2025)
General Background: Adolescence is a developmental phase characterized by rapid social and emotional changes in which peer conformity frequently emerges as adolescents attempt to gain acceptance within social groups. Specific Background: Peer conformity among students is associated with internal psychological factors, including self-concept and emotional intelligence, which shape behavioral adaptation and social interaction. Knowledge Gap: Although prior studies have examined peer conformity, limited empirical evidence simultaneously analyzes the combined relationship of self-concept and emotional intelligence with peer conformity among junior high school students. Aims: This study aims to determine the relationship between self-concept and emotional intelligence with peer conformity among students at State Junior High School 2 Tanggulangin. Results: Using a quantitative correlational design with 265 students selected through stratified random sampling, data were collected using the Tennessee Self Concept Scale Second Edition Short Form, an emotional intelligence scale, and a peer conformity scale, all demonstrating acceptable reliability. Multiple correlation analysis revealed a positive and statistically significant relationship between self-concept and emotional intelligence with peer conformity (R = 0.447; significance = 0.000 < 0.05), with a contribution value of 20%. Novelty: This study provides integrated empirical evidence demonstrating the simultaneous association of self-concept and emotional intelligence with peer conformity among junior high school students using validated psychological instruments. Implications: The findings highlight the importance of developing psychological attributes related to self-perception and emotional regulation as considerations in student social behavior development and educational psychological interventions. Highlights: Psychological Attributes Jointly Show a Statistically Significant Association With Group Behavioral Alignment. Internal Student Characteristics Collectively Account for 20% Variance in Social Adjustment Patterns. Most Participants Demonstrate Moderate Levels Across Measured Psychosocial Dimensions. Keywords: Peer Conformity, Self-Concept, Emotional Intelligence, Adolescents, Junior High Students